Drivers of sustainable innovation strategies for increased competition among companies - Lopes, João M. (2022)
The present study aims to analyse the sustainable innovation strategies that companies can implement in their business models in order to improve their economic performance and become more competitive in the marketplace. This study uses a qualitative methodology based on the case method of nine companies. It was concluded that companies have concerns about environmental issues, translated into the implementation of sustainable practices in their business models, not because they are legal obligations, but because they incorporate sustainability in their strategic vision. Thus, companies add considerable value to their value chain and obtain a better strategic positioning in relation to competitors. It was also found that companies intend to implement innovative sustainable practices and that some companies have a business model that already incorporates sustainability strategies. Additionally, concerning sustainable innovation, we concluded that companies innovate in the manufacturing process (producing more with less) and with the product (modifying their product to make it more sustainable and greener). However, companies generally adopt a defensive sustainability strategy. This article is original because it simultaneously contributes to the development of the literature on sustainable innovation, sustainable strategies and company performance. It also recommends that companies improve their sustainable innovation strategies in business models to obtain a sustainable competitive advantage.